Madrasah Berjalan - Moh. Yusuf (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Madrasah Berjalan (The Walking Islamic School) is another term for khuruj fi sabilillah by Jamaah Tabligh as the mission of educating ummah. It was born out of dissatisfaction with the existing madrasahs preoccupied with the classroom and paid little attention to the faith and religius matters of society in general. Through the Madrasah Berjalan one only focuses on improving his or her faith and studying his or her religion. In addition, one can directly practice and communicate what he or she learns to the surrounding community. Ideally, in term of its participants, a Madrasah Berjalan has at least an educated person in Islamic Studies and a hafidz (memorant of Qur’an). The study period of time in the Madrasah Berjalan is only one tenth of total time a person has. In addition to learning and preaching (tabli>gh), its activities include visiting scholars to grasp knowledge and benefit from them. Dhikr is an individual and/or collective activity that is also emphasized in the Madrasah Berjalan. It is hoped thatwhen coming back from the Madrasah Berjalan to their home, the participantsare really able to renew their faith and are istiqa>mah (committed) in their maqami activities.